2015
DOI: 10.5194/os-11-83-2015
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for correcting fluorescence quenching

Abstract: International audienceUnder high light intensity, phytoplankton protecttheir photosystems from bleaching through nonphotochemicalquenching processes. The consequence ofthis is suppression of fluorescence emission, which mustbe corrected when measuring in situ yield with fluorometers.We present data from the Southern Ocean, collectedover five austral summers by 19 southern elephant sealstagged with fluorometers. Conventionally, fluorescence datacollected during the day (quenched) were corrected using thelimit o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 60 publications
(94 reference statements)
2
54
0
Order By: Relevance
“…The net result is a decrease in fluorescence yield per unit chlorophyll in surface waters during daytime periods of increased irradiance. If left uncorrected, daytime fluorescence will generate approximations of chlorophyll concentration that under‐represent the true values (Biermann et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The net result is a decrease in fluorescence yield per unit chlorophyll in surface waters during daytime periods of increased irradiance. If left uncorrected, daytime fluorescence will generate approximations of chlorophyll concentration that under‐represent the true values (Biermann et al ).…”
Section: Introductionmentioning
confidence: 99%
“…On the vertical scale, quenched fluorescence profiles are also problematic as they have the same shape as profiles that exhibit deep chlorophyll maxima (DCM). DCM are important to pelagic food webs and integrated rates of net primary production (Biermann et al ), and their existence varies from persistent to rare in regions such as the North Atlantic and Southern Ocean, respectively (Holm‐Hansen and Hewes ; Poulton et al ). Even in regions where DCM are rare, recent studies have indicated that highly dynamic mixing and settling regimes of heavily silicified species alongside chlorophyll packaging effects with depth (Behrenfeld and Boss ), mean that any assumption of homogeneity is potentially problematic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glider fluorescence data were first corrected for quenching using a time and depth dependent night-time ratio of optical backscatter to fluorescence corrected from the 3 channels of the ECO puck as per Hemsley et al (2015;our Fig. 2); no quenching could be detected below the euphotic depth (1% surface light), indicating that the process was able to accurately identify quenching-affected portions of the water column (Biermann et al 2015). Quenchingcorrected fluorescence was then converted to chl a values using a scale factor determined by regressing the light attenuation profile from the PAR sensor to the theoretical light attenuation profiles calculated from the fluorescence profiles and attenuation coefficients.…”
Section: Glider Observationsmentioning
confidence: 99%
“…The sensors emit light in the blue to excite chl a fluorescence and measure the resulting emissions in the red. Phytoplankton adapts to specific light regimes and suffers from quenching when exposed to excessive light (Biermann et al 2015). The glider fluorescence data were first corrected for quenching using a time and depth dependent night-time ratio of optical backscatter to fluorescence corrected from the 3 channels of the ECO puck as per Hemsley et al (2015;our Fig.…”
Section: Glider Observationsmentioning
confidence: 99%